American Transfer Policies : Costs and Benefits - Glueck, William (Relations industrielles / Industrial Relations, 1971)
This article reviews Canadian-American business relations, describes how Canadian can be affected by transfer policies, discusses the causes, the costs and benefits of this policy and examines some policy implications for personnel administration in Canada and the United States.